Analisis Faktor Yang Berhubungan Dengan Pemanfaatan Layanan Kesehatan Gigi Dan Mulut Di Puskesmas Kota Banjarmasin - Andriyani, Putri Dwi; Adhani, Rosihan; Nugroho, Adi Nugroho; Noor, Meitria Syahadatina; Musafaah, Musafaah (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2025)
Based on the 2018 Riskesdas, South Kalimantan Province had almost 60% of health problems, while Banjarmasin City had the highest percentage of oral and dental diseases (38.2%). The purpose of this study is to determine the correlation between the use of oral health services at the Banjarmasin City Health Center and factors such as accessibility to information, the availability of dental professionals, insurance coverage, medical facilities, income, and educational attainment. This study's design was cross-sectional. The Banjarmasin City Health Center housed ninety-seven research participants. The following variables' p values were found using multiple logistic regression and chi square analysis results: income (p=0.0221), insurance membership (p=0.0005), dental medical personnel availability (p=0.0005), education level (p=0.0005), and ease of information (p=0.000). The degree of education (Exp(B)=25.410) is the factor that most affects the use of oral health services at the Banjarmasin City Health Center. The results of this study indicate that the use of oral health services is correlated with factors such as insurance coverage, accessibility to dental professionals, degree of education, and health facilities. At the Puskesmas of Banjarmasin, there is, however, no correlation between income and the use of oral health service